2006
DOI: 10.1002/j.1681-4835.2006.tb00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Evaluating Land Use/ Land Cover Change Using Participatory Geographic Information System (PGIS) Tools: A Case Study of Begasheka Watershed, Tigray, Ethiopia

Abstract: Agricultural land degradation in Ethiopia leads to an annual loss of roughly 2 million cubic meters of top soil. The relationship between this loss of soil quality and declining agricultural productivity is increasingly threatening rural livelihoods, putting pressure on urban centres as people migrate, as well as on very scarce forest resources on which the agricultural systems eventually depend Attempts to address land degradation have required the government of Ethiopia to fully understand the underlying soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…Once the maps were drawn, discussions were carried out focusing on the accuracy of the mental maps for Pakasse and Entasopia and modifications were made until there was consensus among the participants. Similar procedures were followed by Aynekulu et al (2006). The main land uses inserted in the maps included cropland, forestland, bareland, open water, swamps and grasslands and settlements.…”
Section: Methodology Land Use and Land Cover Change Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Once the maps were drawn, discussions were carried out focusing on the accuracy of the mental maps for Pakasse and Entasopia and modifications were made until there was consensus among the participants. Similar procedures were followed by Aynekulu et al (2006). The main land uses inserted in the maps included cropland, forestland, bareland, open water, swamps and grasslands and settlements.…”
Section: Methodology Land Use and Land Cover Change Analysismentioning
confidence: 99%
“…Compared to other similar studies (Mbau et al, 2013;Aynekulu et al, 2006) the approach can facilitate the bottom transmission of information thus influencing the process of decision making using bottom up approach including gender representation by involving both men and women sketching the mental maps. This application of PGIS attempts to reduce the implementation of imposed solutions that do not represent or reflect public concerns.…”
Section: Trends In Land Use and Land Cover Change In Pakasse And Entamentioning
confidence: 98%
“…The first sample plot was placed randomly, following systematic sampling procedure with 100 m interval between plots of the same transect [14,17]. All tree diameters in the larger plot were measured at breast height (DBH) (1.3 m aboveground level) and at stump height (DSH) (30 cm aboveground level) [18].…”
Section: Sampling and Data Collection Methodsmentioning
confidence: 99%
“…Until the recent massive plantations, the northern highlands in general and Tigray in particular have been devoid of vegetation cover. A watershed scale investigation by Aynekulu et al [12] indicated that 75% of the forest land had been converted into arable land over a period of 50 years. Studies carried out in the northwestern highlands of Ethiopia indicate a considerable decline in the natural forest cover and expansion of cultivated land [13][14][15].…”
Section: The Climate Change Perspectivementioning
confidence: 99%